Effect of intense electron and ion irradiation on optical absorption of boron carbide thin films; Radiation Effects and Defects in Solids: Incorporating Plasma Science and Plasma Technology; Vol. 173, iss. 11-12 - Remnev G. E. Gennady Efimovich; Musil J. Jindrrich; Tarbokov V. A. Vladislav Aleksandrovich; Pavlov S. K. Sergey Konstantinovich; Konusov F. V. Fedor Valerievich; Egorov I. S. Ivan Sergeevich; Gadirov R. M. Ruslan Mukhamedzhanovich; Kabyshev A. V. Alexander Vasilievich; Javdosnak D. Daniel; Zenkin S. P. Sergey Petrovich (2018, 2018)
Title screen